Utilization of high carbon fly ash and copper slag in electrically conductive controlled low strength material. (30th December 2017) - Lim, S.; Lee, W.; Choo, H.; Lee, C.
Highlights: Both high carbon fly ash (HCFA) and copper slag (CS) are electrically conductive. Both HCFA and CS are waste materials with low reuse rate. CS was reused as a substitute for a fine aggregate in the CLSM. Electrically conductive CLSM was developed using both HCFA and CS. Various experiments were performed on the developed CLSM. Abstract: The aim of this experimental investigation is to develop electrically conductive controlled low strength materials (CLSM) using both fly ash with high content of unburned carbon particles (HCFA) and copper slag as a fine aggregate, both of which are waste materials with low reuse rate. Various experiments, including flow consistency test, bulk density measurement, unconfined compression test, and electrical conductivity ( σmix ) measurement were performed on the developed electrically conductive CLSM. For comparison with the results of the developed conductive CLSM, various experiments were also performed on CLSM containing electrically nonconductive particles (low carbon fly ash (LCFA) and sand). The results of this study demonstrate that σmix of the tested CLSM specimens increases with increasing copper slag fraction in aggregate and the measured σmix of the CLSM based on HCFA is greater than that with LCFA because both HCFA (or unburned carbon particles) and copper slag are electrically conductive. The measured flow consistency, bulk density, and unconfined compressive strength (UCS) of conductive CLSM were comparable with those of nonconductive CLSM. Therefore, the electrically conductive CLSM can be developed using both HCFA and copper slag. Finally, the relationship between UCS and 1/ σmix was also investigated in this study.